2020
DOI: 10.36680/j.itcon.2020.014
|View full text |Cite
|
Sign up to set email alerts
|

A design review session protocol for the implementation of immersive virtual reality in usability-focused analysis

Abstract: Research and applications related to Virtual Reality (VR) in the Architecture, Engineering, Construction and Facility Management (AEC/FM) industry are steadily increasing, being considered as one of the current trends in digital innovation. A convergence is currently on-going between Building Information Modelling (BIM), VR implementation and the soft landings principles, which highlight the need for a smooth transition from design to operation through the early involvement of clients and end-users. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Vergara et al [27] considered realism and interaction as key considerations for developing VR experiences in engineering education, but driven by the specific objectives as the first step to determine the usefulness of VR before proceeding with the technical design and user evaluation. Mastrolembo Ventura et al [28] looked more broadly at both technological and procedural challenges when implementing VR in design reviews.…”
Section: Virtual Reality As An Interactive Spatial and Social Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Vergara et al [27] considered realism and interaction as key considerations for developing VR experiences in engineering education, but driven by the specific objectives as the first step to determine the usefulness of VR before proceeding with the technical design and user evaluation. Mastrolembo Ventura et al [28] looked more broadly at both technological and procedural challenges when implementing VR in design reviews.…”
Section: Virtual Reality As An Interactive Spatial and Social Experiencementioning
confidence: 99%
“…While recent studies have begun to address the need for VR implementation protocols for design reviews [28], crafting the narrative structure of the VR experience itself requires an understanding of user tasks, behavior, and perception in order to determine which elements are critical to include in models to maintain control.…”
Section: The Purpose Of the Vr Experiencementioning
confidence: 99%
“…Project communication was enhanced by Dinis et al's [74] new workflow, which coupled laser scanning and virtual reality (VR) within building information modelling (BIM) and brought an alternative approach regarding the definition of expected requirements, qualities, and specifications valued by stakeholders (i.e., project owners). Similarly, Ventura et al [75] formed a process map representing all the necessary phases and activities to consider for the effective adoption of immersive VR to evaluate design intents with clients and end-users. The investigation of Abbas et al [76] showed no large statistical difference in IVR-based and face-to-face (FtF) communication in terms of discussion quality, communication richness, and openness, but FtF did show slightly better results, and this led to the conclusion that immersive reality needs improvement to better represent realistic interactions.…”
Section: Virtual and Augmented Reality (Vr/ar) As Means To Enhance Collaboration In Design Phase And Involve End-users In Early Project Pmentioning
confidence: 99%
“…The usage of virtual reality and similar technologies (e.g., AR and MR) has risen in recent years, but it is still relatively new ICT in the AEC industry, and at this stage of development, technology is quite expensive [40,76]. Zaker and Coloma [71] highlighted that further research and development should deal with making these technologies more affordable, while Ventura et al [75] call for an appropriate framework for measuring the actual added value of VR systems implementation. There is room for various improvements to make VR/AR more adjusted to the communication needs of AEC industry stakeholders [71], and one research stream should deal with improving the accuracy of the data collected and analyzed in such environments so that they represent physical environments more realistically [69,101].…”
Section: Bim Collaboration As Means Of Engagement and Integration Of Internal Construction Project Stakeholdersmentioning
confidence: 99%
“…The themes addressed in this literature range from immersiveness, experience, complexity, spatial perception and cognition, problem solving, decision-making, collaboration, user engagement, to value and cost or time. Overall, these studies suggest the potential of visualisation and collaboration environments to support the creation, communication, development and understanding of design through supporting and extending other design procedures (Whyte and Nikolic, 2018; Ventura et al, 2020;Goulding and Rahimian, 2015). However, much of the literature focusses on developing/ testing technology in experimental studies, or examining the practical use of immersive technology using standard metrics.…”
Section: Introductionmentioning
confidence: 99%